(untitled) (Indian Journal of Child Health, 2019)
Background: Zinc deficiency is associated with high rates of infections such as diarrhea, skin, and respiratory infections. Objective: The objective of the study was to determine serum zinc levels in children hospitalized with pneumonia and to study the correlation between serum zinc levels and severity and complications of pneumonia. Materials and Methods: A cross-sectional study was conducted in a hospital of South India, which included 120 subjects aged between 6 months and 5 years. A detailed history, clinical examination, severity of pneumonia according to the WHO criteria, chest X-ray findings, arterial oxygen saturation, hemoglobin, and total white blood cell count were noted. Results: Mean serum zinc levels in pneumonia cases were significantly lower compared to healthy age- and sex-matched controls (p=0.001). Low serum zinc was associated with increasing severity of pneumonia. Serum zinc levels in pneumonia, severe pneumonia, and very severe pneumonia were 118.4, 67.7, and 45.7 ?g/dl, respectively. Out of 60, 3 were complicated with empyema and 3 cases expired. The mean serum zinc levels in cases complicated with empyema and in expired cases were very low compared to those with no complications. Conclusions: Serum zinc level is low in children with pneumonia and lower serum zinc is associated with increased severity of pneumonia.